2023
DOI: 10.3390/coatings13101663
|View full text |Cite
|
Sign up to set email alerts
|

New Progress in the Application of Flame-Retardant Modified Epoxy Resins and Fire-Retardant Coatings

Shuang Sun,
Qiangliang Yu,
Bo Yu
et al.

Abstract: Due to the enhancement of people’s environmental awareness, flame-retardant epoxy resin (EP) tends to be non-toxic, efficient, and multi-functional, and its development is systematic. At present, many new flame retardants or intrinsic modification methods reported in studies can effectively improve the flame retardability and thermal stability of EP. However, many aspects still need to be further improved. In this review, the flame-retardant mechanism and method of flame-retardant epoxy resins are briefly anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 131 publications
(167 reference statements)
0
2
0
Order By: Relevance
“…The tested filler contents were selected based on the data reported in the literature [ 56 , 58 ] on the modification of epoxy compounds with various fillers. Studies [ 50 , 51 ] were conducted with the use of various amounts of fillers, including flame retardants, depending on the resin type. Also, patent descriptions (PL 230,340 B1, PL 214,525 B1) provide information about the addition of antipyrine to epoxy resin in amounts ranging from 1 to 2%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tested filler contents were selected based on the data reported in the literature [ 56 , 58 ] on the modification of epoxy compounds with various fillers. Studies [ 50 , 51 ] were conducted with the use of various amounts of fillers, including flame retardants, depending on the resin type. Also, patent descriptions (PL 230,340 B1, PL 214,525 B1) provide information about the addition of antipyrine to epoxy resin in amounts ranging from 1 to 2%.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that boric acid is used as an additive that reduces the flammability of polymers [ 42 , 45 , 51 , 52 , 53 ], e.g., polyurethane or polyurethane–polyisocyanurate foams [ 44 ], as well as of epoxy composites [ 42 , 43 ]. Paciorek-Sadowska et al [ 44 ] found that the application of borate as a polyol component and, simultaneously, as a flame retardant in the recipe for the production of PUR-PIR foams was very favorable.…”
Section: Introductionmentioning
confidence: 99%